LINKING BUSINESS STRATEGIES AND DIGITAL MARKETING TO COMPETITIVE ADVANTAGE IN LOCAL CAFES IN MALAYSIA - Halid, Hafinas; Mohd Yusoff, Yusmani; Nowalid, Wan Aishah Wan Mohd; Johari, Nurul Aina (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
The cafe industry in Malaysia has experienced rapid growth over the past decade, driven by lifestyle changes, urbanization, and the increasing popularity of coffee culture. However, these cafes face intense competition from international brands and market saturation, signals the imperativeness in identifying effective strategies for sustainable competitiveness. This concept paper examines the relationship between business strategies and competitive advantage among local cafes in Malaysia, with a focus on the moderating role of digital marketing. Drawing on Porter’s Generic Strategies cost leadership, differentiation, and focus and the Dynamic Capabilities Theory, this concept paper proposes that digital marketing strengthens the impact of strategic choices on competitive advantage. Cost leadership allows cafes to attract price-sensitive customers through efficiency, while differentiation emphasizes unique offerings and brand identity, and targets niche markets with tailored experiences. Digital marketing, encompassing social media, e-commerce, and online customer engagement, enhances these strategies by improving visibility, customer relationships, and market adaptability. It enables cafés to sense opportunities, respond swiftly to consumer trends, and reconfigure resources to sustain performance. The proposed framework highlights that digital marketing is a strategic enabler that amplifies the effectiveness of business strategies. This study contributes to the literature review by understanding how local cafes can leverage strategic and digital capabilities to build lasting competitive advantages in an increasingly digitalized and competitive environment. Future empirical research is recommended to validate the proposed model and guide local cafe owners in developing integrated strategic and digital approaches for long-term success.